High nonnucleoside reverse transcriptase inhibitor resistance levels in HIV-1-infected Zambian mother–infant pairs. (1st October 2020) - Bennett, Sydney J.; Chunda-Liyoka, Catherine; Poppe, Lisa K.; Meinders, Katie; Chileshe, Chisanga; West, John T.; Wood, Charles
Abstract : Objective(s): To elucidate relationships in antiretroviral resistance between HIV-1-infected mother–infant pairs by defining the resistance profiles in the mothers and infants and quantifying drug resistance prevalence in the pairs post-Option B+ implementation. Design: Collection of dried blood spots from mother–infant pairs during routine HIV-1 screens in Lusaka, Zambia from 2015 to 2018. Methods: DNA was extracted from the dried blood spots, the HIV-1 pol region was amplified, and the purified proviral DNA was sequenced using Sanger sequencing. Drug resistance mutations (DRM) were identified in sequenced DNA using the Stanford HIVdb (https://hivdb.stanford.edu/ ). Results: DRM were detected in 45% (44/97) of samples, and these samples were found to harbor resistance to at least two antiretrovirals. The prevalence of nonnucleoside reverse transcriptase inhibitor resistance was significantly higher than that of other antiretroviral classes. DRM were detected disproportionately in infants (67%; 33/49) compared with mothers (23%; 11/48), but the magnitude of resistance did not differ when resistance was detected. The disparity in drug resistance profiles was reinforced in pairwise comparison of resistance profiles in mother–infant pairs. Conclusion: While Option B+ is effective in reducing mother-to-child transmission, in cases where this regimen fails, high-level nonnucleoside reverse transcriptase inhibitor resistance is frequently detected in infants. This underscores the importance of pretreatment drug resistance screening in both mothers and infants and emphasizes the necessary change to protease inhibitor-based and integrase inhibitor-based regimens for treatment of HIV-1-infected infants and mothers. Abstract : Supplemental Digital Content is available in the text